Formulation and Test of Antioxidant Activity of Serum Active Fraction of Red Pomegranate Skin Extract (Punica granatum L.) by FRAP Method (Ferric Reducing Antioxidant Power) - Thianika Shalsabillah Armandoko; Senda Kartika Rakainsa (Journal of Science and Technology Research for Pharmacy, 2025)
Aging of the body occurs with age, which can be seen in the skin. Skin aging is a physiological process that occurs in the human body. Free radicals are one of the causes of skin aging. By using antioxidant compounds, you can stop the increase in free radicals. Red pomegranate peel extract (Punica granatum L.) is one of the natural ingredients for a natural antioxidant, cause it’s contains polyphenols such as tannins. The aim of this research was to determine the fraction of pomegranate peel extract with the highest antioxidant activity and to determine the optimal serum formula for the red pomegranate peel fraction. The antioxidant activity testing method used in this research is the FRAP method (ferric reducing antioxidant power). The sample extract is fractionated, and then the fraction that has the highest antioxidant activity is made into a serum preparation formulation and preparation evaluation test. Based on the results of total tannin levels in all samples also showed positive results with a change in the color of the solution to bluish. The results of the antioxidant activity of all samples were categorized as very strong antioxidants as stated in the IC value50 < 50 ppm. Optimizing the antioxidant serum formulation used HPMC concentrations of 0.5%, 1% and 2% respectively. The results obtained from testing antioxidant activity obtained IC values50 the best was 0.368 ppm for the ethyl acetate fraction of red pomegranate peel. Optimizing the serum formula used a HPMC concentration of 1%, with an IC value50 amounting to 133,903 ppm.